Causes of medication administration errors and barriers to reporting as perceived by nurses in Saudi Arabia: A qualitative study - Alotiabi, Jazi Shaydied (Belitung Raya Foundation, Indonesia, 2024)
Background: Medication administration errors significantly impact patient safety, potentially leading to severe harm or fatality. Reporting such errors through active systems improves medication administration, thereby enhancing patient safety and the quality of care. However, in the context of Saudi Arabia, little is understood about the causes of medication administration errors and the obstacles hindering their reporting. Objective: This study aimed to explore nurses’ perceptions of the causes of medication administration errors and the barriers to reporting them. Methods: The study employed a qualitative descriptive design, conducting face-to-face semi-structured interviews with 43 nurses from three hospitals in Taif Governorate, Saudi Arabia, between October and November 2023. Purposive sampling was used to recruit participants, and thematic analysis was utilized for data analysis. Results: The following themes emerged regarding the causes of medication administration errors: order deficiencies, high workloads and staff shortages, and malpractice. Regarding the barriers to reporting errors, the emerging themes were fear of punishment and lack of support, lack of knowledge and awareness about reporting, and lack of feedback. Conclusion: This study reveals nurses’ perceptions of the causes of medication administration errors and the barriers to reporting them. Recognizing and addressing these causes and barriers are essential for patient safety and the improvement of the healthcare environment. Efforts should be directed toward implementing interventions that address high workloads, enhance staff education and awareness, and promote a workplace culture conducive to reporting errors without fear of repercussions. Additionally, supportive mechanisms, such as feedback systems and resources for professional development, should be implemented to empower nurses to actively participate in error reporting and contribute to continuous improvement in medication administration practices.